Cardiovascular magnetic resonance imaging (MRI) - Botnar, René M.; Makowski, Markus R. (Elsevier Inc., 2014)
Cardiovascular disease is the leading cause of morbidity/mortality in the western world. Atherosclerotic plaques are the main culprit of myocardial infarction and stroke. Magnetic resonance imaging is an emerging clinical tool for the detection and characterization of atherosclerotic plaques. Target-specific molecular MR contrast agents allow the characterization of plaques on a molecular and cellular level. This chapter starts with an overview of the biological changes leading to atherosclerosis. The basic principles of molecular MR are discussed and different MR sequences are introduced. This chapter concludes with a discussion of clinically-feasible aortic, carotid and coronary MR imaging techniques. © 2014 Woodhead Publishing Limited All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Cardiovascular magnetic resonance imaging; Contrast agents